PENGELOLAAN MANAJEMEN RISIKO OPERASIONAL MENGGUNAKAN APLIKASI PRIMA DENGAN PENDEKATAN HOR DAN FMEA DI PT.XYZ - Siregar, Muhammad Fathurrahman; Agriva Diansyah Putra; Sembiring, Anita Christine (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze operational risks in receivables management at PT XYZ using Failure Mode and Effect Analysis (FMEA) and House of Risk (HOR) methods. Data were obtained from the Prima Application and internal company documents. The FMEA method was used to identify risk priorities based on the Risk Priority Number (RPN), while HOR was used to determine mitigation strategies based on Aggregate Risk Priority (ARP) and Effectiveness to Difficulty (ETD). The results indicate that the main risks include payment delays, administrative errors, and customers’ inability to fulfill payment obligations. The primary causes are weak customer verification, ineffective credit policies, and lack of receivables monitoring. Priority mitigation strategies include routine receivables monitoring, implementation of invoice SOPs, and stricter credit policies. The combination of both methods provides a more comprehensive and effective risk analysis. Keywords: operational risk, FMEA, House of Risk, risk mitigation, receivables